PERAN PEMERINTAH DAERAH DALAM PENANGGULANGAN KEMISKINAN MELALUI PROGRAM PENINGKATAN KETERAMPILAN DI KOTA MEDAN - Mutia Sari Lubis; Irsyad Lubis (Jurnal Ekonomi STIEP, 2020)
Since 2015 the local government of Medan City has determined that poverty alleviation and community empowerment efforts become one of the regional priority programs. This program is contained in Medan City Regulation No. 5 of 2015. This study aims to determine the role of the City Government in poverty reduction through the Skills Improvement program in Medan and the factors that influence it. To achieve these objectives, qualitative research methods are used to decipher data descriptively. Data collection techniques are done by observation, interviews, and documents and archives using qualitative descriptive analysis techniques. The results showed: First, the role of the government in empowering the poor through the Skills Improvement program can be broadly categorized into two roles, namely the growth of the business climate and the strengthening of business potential or power. The growth of the business climate includes funding, facilities & infrastructure, business information, business licensing and trade promotions. While Strengthening Potential or Power covers production and processing, marketing, and human resources. Second, the factors that influence the empowerment of the poor through the Skills Improvement program in Medan include inhibiting and supporting factors. The inhibiting factor is the lack of innovation in marketing and the limited budget which is only a few percent, while the supporting factors are human resources and abundant natural resources.